FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KOPERASI PONDOK PESANTREN - Gunawan Aji (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
Some problems are still coming up in developing boarding school cooperative. Quality of human resources, participation and performance of cooperative boarding school are some among so many problems are actually there. Strategy to improve the performance of cooperative boarding school is very urgent through participation, commitment and ability to keep innovative among members.